2010
DOI: 10.1186/1475-2859-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Zygosaccharomyces bailii GAS 1 homologue and effect of cell wall engineering on protein secretory phenotype

Abstract: BackgroundZygosaccharomyces bailii is a diploid budding yeast still poorly characterized, but widely recognised as tolerant to several stresses, most of which related to industrial processes of production. Because of that, it would be very interesting to develop its ability as a cell factory. Gas1p is a β-1,3-glucanosyltransglycosylase which plays an important role in cell wall construction and in determining its permeability. Cell wall defective mutants of Saccharomyces cerevisiae and Pichia pastoris, deleted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…However, one would imagine that even longer flanking regions could help to raise the frequency of the event, which in our case remained low. Remarkably, we found that the deletion of another, nonessential, gene (ZbGAS1) required only about 400-bp-long flankings (Passolunghi et al, 2010), in agreement with the data of Mollapour & Piper (2001). The targeted gene replacement can be considered a corruption of the repair process of DNA double-strand breaks by homologous recombination, as it leads to permanent loss of the targeted chromosomal region rather than restoration of a damaged sequence (Rothstein, 1983;Langston & Symington, 2005).…”
Section: Auxotrophic Mutantsupporting
confidence: 87%
See 1 more Smart Citation
“…However, one would imagine that even longer flanking regions could help to raise the frequency of the event, which in our case remained low. Remarkably, we found that the deletion of another, nonessential, gene (ZbGAS1) required only about 400-bp-long flankings (Passolunghi et al, 2010), in agreement with the data of Mollapour & Piper (2001). The targeted gene replacement can be considered a corruption of the repair process of DNA double-strand breaks by homologous recombination, as it leads to permanent loss of the targeted chromosomal region rather than restoration of a damaged sequence (Rothstein, 1983;Langston & Symington, 2005).…”
Section: Auxotrophic Mutantsupporting
confidence: 87%
“…For example, in the nonconventional yeast Hansenula polymorpha, flanking regions of at least 1 Kbp seem to be a key factor in obtaining satisfactory homologous recombination efficiency (about 50%) (Gonzalez et al, 1999). Remarkably, we found that the deletion of another, nonessential, gene (ZbGAS1) required only about 400-bp-long flankings (Passolunghi et al, 2010), in agreement with the data of Mollapour & Piper (2001). Hence, it appears that the length of homologous recombinogenic flanking regions has to be optimized for each individual organism.…”
Section: Auxotrophic Mutantmentioning
confidence: 71%
“…Deletion of GAS1 in S. cerevisiae resulted in an almost 7-fold increase in the level of human hIGF1 29 . Similarly, secreted enzymatic activity was almost doubled when GAS1 was deleted in Z. bailii producing C. rugosa lipase Crl1p or Y. lipolytica protease Xpr2p 31 . In A. fumigatus , an increase in glycoprotein secretion has also been reported for gel2 Δ mutants 46 …”
Section: Discussionmentioning
confidence: 75%
“…Therefore, there may still be sufficient protein in the wall of the Aggas1A Δ mutant to explain the lack of improved secretion. It is worth noting that also in P. pastoris the disruption of GAS1 had no effect on the secretion of human trypsinogen or human serum albumin, although the amount of R. oryzae lipase released from the cells was doubled 31 . Similarly, GAS1 deletion in Z. bailii did not increase human IL-1b secretion 32 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation